2013
DOI: 10.2478/plc-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences and Quality Of Translation: A Personality-Based Perspective

Abstract: The current study was targeted at investigating the relationship between translation students’ personality types and the quality of their English-to-Persian translations with respect to different text types. To this aim, 35 undergraduate senior students of translation were randomly sampled. To obtain some demographic information about the participants, the researchers used a background questionnaire. The participants were given three different text types for the translation task. An advertisement, a scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…In agreement with the same token, the influence of aspects of personality on the quality of translation task has been confirmed by numerous studies conducted in the realm of translation studies (e.g. Reiss, 1971Reiss, , 2004Karimnia & Mahjubi, 2013;Kussmaul, 1995;Pourgharib & Dehbandi, 2013;Hubscher-Davidson, 2009. These finding signify the role of translators' personality on the decisions they make in the process of translation, which in turn ultimately affect the quality of the produced translations.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In agreement with the same token, the influence of aspects of personality on the quality of translation task has been confirmed by numerous studies conducted in the realm of translation studies (e.g. Reiss, 1971Reiss, , 2004Karimnia & Mahjubi, 2013;Kussmaul, 1995;Pourgharib & Dehbandi, 2013;Hubscher-Davidson, 2009. These finding signify the role of translators' personality on the decisions they make in the process of translation, which in turn ultimately affect the quality of the produced translations.…”
Section: Discussionsupporting
confidence: 67%
“…It included questions about the translation difficulties, their opinions on enjoyment of the translation, and the like. The questionnaire was designed and applied by Orozco and Albir (2002) and was adopted from Karimnia and Mahjubi (2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of these individual differences and characteristics may directly influence their translation quality (Shojaee & Sahragard, 2012;Karimnia & Mahjubi, 2013;Shangarffam & Abolsaba, 2009;Dongfeng & Dan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Since the TQA matrix is based on comparing the main concepts of the TQA models of House (1977House ( , 1997House ( , 2015 , Nord (1991Nord ( , 1997Nord ( , 2005, and Colina (2008Colina ( , 2009Colina ( , 2015, providing students with such a matrix prior to the translation process can help them understand not only the concept of translation, but also the requirements of translation quality. In this respect, research (Angelelli, 2009;Colina, 2003;Hague, Melby, & Zheng, 2011;Karimnia & Mahjubi, 2013;Moskal, & Leydens,2000;Tomlinson & Moon, 2013) concluded that assessment tools should not only measure students' levels, but also recognize their progress and guide them to produce a high quality product.…”
Section: Implications and Recommendationsmentioning
confidence: 99%